MHO_0730 as a Surface-Exposed Calcium-Dependent Nuclease of Mycoplasma hominis Promoting Neutrophil Extracellular Trap Formation and Escape. (17th August 2019) - Cacciotto, Carla; Dessì, Daniele; Cubeddu, Tiziana; Cocco, Anna Rita; Pisano, Andrea; Tore, Gessica; Fiori, Pier Luigi; Rappelli, Paola; Pittau, Marco; Alberti, Alberto
Abstract: Mycoplasma lipoproteins play a relevant role in pathogenicity and directly interact with the host immune system. Among human mycoplasmas, Mycoplasma hominis is described as a commensal bacterium that can be associated with a number of genital and extragenital conditions. Mechanisms of M. hominis pathogenicity are still largely obscure, and only a limited number of proteins have been associated with virulence. The current study focused on investigating the role of MHO_0730 as a virulence factor and demonstrated that MHO_0730 is a surface lipoprotein, potentially expressed in vivo during natural infection, acting both as a nuclease with its amino acidic portion and as a potent inducer of Neutrophil extracellular trapsosis with its N-terminal lipid moiety. Evidence for M. hominis neutrophil extracellular trap escape is also presented. Results highlight the relevance of MHO_0730 in promoting infection and modulation and evasion of innate immunity and provide additional knowledge on M. hominis virulence and survival in the host. Abstract : Mycoplasma lipoproteins play a relevant role in pathogenicity. In this study we investigate the role of Mycoplasma hominis MHO_0730 as a virulence factor. Results highlight the relevance of MHO_0730 in promoting infection and modulating and evading the host immune response.